Critical evaluation of peripheral smear in cases of anemia with high mean corpuscular hemoglobin concentration in children: A series of four cases - Sharma Sunita (Indian Journal of Pathology and Microbiology, 2010)
Mean corpuscular hemoglobin concentration (MCHC), a parameter that is reported as a part of a standard complete blood count by automated analyzer, is a measure of the concentration of hemoglobin in a given volume of packed red blood cell. Values of MCHC significantly above reference range are not physiologically possible due to limitations on solubility of hemoglobin. The high MCHC can give us a clue to certain type of hemolytic anemia and necessitate critical evaluation of peripheral smear to reach a definitive diagnosis. Here we are presenting a series of four cases with raised MCHC, emphasizing the importance of systematic and meticulous examination of the peripheral smear to render a definitive diagnosis.